Global Salmonidae introductions reveal stronger ecological effects of changing intraspecific compared to interspecific diversity. (21st September 2016) - Buoro, Mathieu; Olden, Julian D.; Cucherousset, Julien
Abstract: The introduction of organisms within the native range of wild conspecifics is a widespread phenomenon and locally modifies patterns in intraspecific diversity. However, our knowledge of the resulting ecological effects, as opposed to those caused by invasion‐induced changes in interspecific diversity, is still limited. Here, we investigated the ecological effects of native and non‐native invaders across levels of biological organisations and recipient organisms using the global and long history introductions of salmonids. Our meta‐analysis demonstrated that the global effects of native species introductions exceeded those induced by non‐native invaders. The impacts of native invaders were primarily manifested at the individual level on wild conspecifics, but remained largely unexplored on other native organisms and at the community and ecosystem levels. Overlooked and poorly appreciated, quantifying the impacts of native invaders has important implications because human‐assisted introductions of domesticated organisms are ubiquitous and likely to proliferate in the future.